2018
DOI: 10.3390/inventions3020032
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Micro Channel Heat Sink by Combing Genetic Algorithm with the Finite Element Method

Abstract: Abstract:The design of a micro multi-channel heat sink to achieve the minimum thermal resistance is the purpose of this study. The numerical package is employed by using the genetic algorithm to process the heat dissipation optimization of the micro multi-channel heat sink (the genetic algorithm employs the numerical package). The variables of this optimal design include channel number, channel aspect ratio and the ratio of channel width to pitch, as well as considering the weight of this micro channel heat si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…After analyzing the correlation coefficient and signalto-noise ratio, their results showed that the Taguchi experiment model may have some limitations in detecting the edge of process space. Lin et al [105] combined the FEM and GA to design a micro multichannel heat sink with minimum thermal resistance, the control parameters such as channel number and channel size were considered as optimisation variables. Their results showed that the thermal resistance was effectively reduced by 0.144 W/K.…”
Section: Taguchi Methods (Tm) and Genetic Algorithms (Ga)mentioning
confidence: 99%
“…After analyzing the correlation coefficient and signalto-noise ratio, their results showed that the Taguchi experiment model may have some limitations in detecting the edge of process space. Lin et al [105] combined the FEM and GA to design a micro multichannel heat sink with minimum thermal resistance, the control parameters such as channel number and channel size were considered as optimisation variables. Their results showed that the thermal resistance was effectively reduced by 0.144 W/K.…”
Section: Taguchi Methods (Tm) and Genetic Algorithms (Ga)mentioning
confidence: 99%
“…The optimized shape is then extended along the flow direction to form the entire channel length without further modifications of the channel passage (to be introduced in Section 3.2.2). Based on the design parametrizations, the studies in this category could be classified into three classes, as shown in Figure 8: (a) optimization of single channel cross-section size/parameter based on a predefined simple geometry [55][56][57][58][59][60][61][62][63][64][65]; (b) optimization of single channel cross-section shape [66,67]; and (c) TO of the entire cross-section of the heat sink [68]. The key step in the optimization is establishing the relationship between the design variables and the objective function, either by direct physics analysis or by constructing a surrogate function.…”
Section: Channel Cross-section Optimizationmentioning
confidence: 99%
“…[27,28]. Several algorithms are suggested towards microchannel fins optimization; however, combination of genetic algorithm with the finite element methods is one of the interesting methods adopted for the thermal optimization of microchannel fins [29]. Another effective approach for the optimization study is the multi-objective optimization via using the weighted sum method with the genetic algorithm [30].…”
Section: Introductionmentioning
confidence: 99%